Power Chain Saw Versus Two Man Cross Cut Saw - a Comparative Study in Felling of Sal (Shorea Robusta) - Kant, Hari; Sood, K. G. (Indian Forester, 1975)
At present, felling in most of the forests in India is being done either by axe, axe and two man cross cut saw or two man cross-cut saw alone, the most common tool being the peg-toothed cross cut saw. Power chain saws have also been occasionally used, but no (scientific planning) of the felling operations has been done anywhere so far. This study has been made to compare the time gained in and the relative economics of felling by Power chain saw as compared to the Raker cutter saw and the Peg-toothed saw. It has been observed that a break-even point between Power chain saw and Raker saw is reached in 20-25cm diameter range and that between Power chain saw and Peg toothed saw is reached in 15-20 cm diamter range. It has also been seen that power chain saw is 27% to 60% more economical in 25-60 cm diameter ranges and 33% to 100% less economical in 10-20 cm diameter ranges as compared to raker saw. As compared to peg toothed saw the power chain saw is 100% costlier in 10-15 cm diameter range and 12% to 71% cheaper for 20 cm to 60 cm diameter range. Peg toothed saw is 14% to 37% costlier as compared to raker saw.